Nonunion of lateral humeral condylar fracture in a child with cubitus varus - Sulaiman, Abdul Razak; Munajat, Ismail; Mohd, Emil Fazliq; Sharifudin, Mohd Ariff (2010)
Patients with cubitus varus deformity secondary to malunited supracondylar fracture are at risk for lateral humeral condylar (LHC) fracture. This report describes a child presenting with preexisting malunion of supracondylar fracture presenting along with nonunion of a LHC fracture following a recent injury. The patient underwent resection osteotomy of the metaphyseal proximal fragment of the fracture surface, reduction of the displaced LHC fragment and screw fixation. This procedure corrected the cubitus varus and treated the nonunion of the lateral condyle thus avoiding a supracondylar osteotomy procedure. Treatment resulted in solid union, good range of motion and no avascular necrosis.